2020
DOI: 10.14533/jbm.20.41
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and catalytic activity of citrus fruits peels mediated nano-flowers

Abstract: In this work, plant extract-metal ions hybrid nanoflowers (HNFs) were synthesized and their catalytic and antimicrobial properties were examined. While the sweet and sour lemon peel extract (acquired in boil water) and its primary elements were engaged as organic elements in the creation of NFs, copper (II) ions (Cu 2+) were the inorganic element. Scanning Electron Microscopy (SEM), Energy-Dispersive X-ray (EDX) spectroscopy, and Fourier Transform Infrared Spectrometry (FT-IR) were examined to characterize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Demirbas (2021) reported that Cu-based NF synthesized with orange peel extract effectively exhibited antimicrobial activity against Yersinia ruckeri strain [11]. The antimicrobial effect of lemon peel extract coordinated Cu NFs against Candida albicans, Staphylococcus aureus, and E. coli strains has been demonstrated [12]. Photocatalytic activities of silver (Ag) NFs synthesized by using Kalanchoe daigremontiana extract against methylene blue dye; antimicrobial activities have been demonstrated against S. aureus, and E. coli strains.…”
Section: Introductionmentioning
confidence: 99%
“…Demirbas (2021) reported that Cu-based NF synthesized with orange peel extract effectively exhibited antimicrobial activity against Yersinia ruckeri strain [11]. The antimicrobial effect of lemon peel extract coordinated Cu NFs against Candida albicans, Staphylococcus aureus, and E. coli strains has been demonstrated [12]. Photocatalytic activities of silver (Ag) NFs synthesized by using Kalanchoe daigremontiana extract against methylene blue dye; antimicrobial activities have been demonstrated against S. aureus, and E. coli strains.…”
Section: Introductionmentioning
confidence: 99%
“…Demirbas (2021) reported that Cu-based NF synthesized with orange peel extract effectively exhibited antimicrobial activity against Yersinia ruckeri strain [10]. The antimicrobial effect of lemon peel extract coordinated Cu NFs against Candida albicans, Staphylococcus aureus, and E. coli strains has been demonstrated [11]. Photocatalytic activities of silver (Ag) NFs synthesized by using Kalanchoe daigremontiana extract against methylene blue dye; antimicrobial activities have been demonstrated against S. aureus, and E. coli strains.…”
Section: Introductionmentioning
confidence: 99%